PENGARUH HARGA JUAL DAN VOLUME PENJUALAN BENANG FILAMEN TERHADAP PENDAPATAN PADA PD. HS PUTRA CIMAHI - HANI HATIMATUNNISANI HANI HATIMATUNNISANI; EUIS HERNAWATI POLITEKNIK EUIS HERNAWATI POLITEKNIK (EKBIS (Ekonomi & Bisnis), 2018)
This research aims to determine the influence of sales price and sales volume of filament yarn towards the company income at the trading company HS. Putra Cimahi. The method used in this research is quantitative method. The research are using secondary data, with sample financial statements from trading company HS Putra period of 2016. Data was analysed using multiple regression to test the effect of independent variables on dependent variable. F-test and t-test was employed to test the hypothesis with 5% level of significant. The result of investigation F-test showed that all independent variables influences significantly on the company income. But t-test showed that sales price not influences significantly on the company income. Lastly the evidence shows that the prediction power of regression model is 65,8% and the rest 34,2% explained by other variables which are not include in this research. Keywords: Sales Price, Sales Volume, Company Income